Psychological Absence of The Father and Its Relationship to The Social Adjustment Among the Children Residing in The Orphanage in Erbil City - Shahzad Ramadan Hasan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This research aimed at identifying the level of the father’s psychological absence, and the level of social adjustment among a sample of children residing in the orphanage in Erbil. It also aimed to identify the relationship between the psychological absence of the father and social adjustment as well as the differences between the answers of the research sample members on the scale of psychological absence of the father and the scale of social adjustment according to two variables: (gender, and the mother’s educational level). The research sample consisted of (65) single sons residing in the orphanage in the city of Erbil. The researcher used the father’s psychological absence scale and the social adjustment scale, which were prepared by the researcher, and the research relied on the descriptive analytical approach.